Survei Sarana dan Prasarana Pendidikan Jasmani di Sekolah Dasar Kecamatan Kedu Kabupaten Temanggung Tahun 2020 (Indonesian Journal for Physical Education and Sport, 2021)
This research based on preliminary observations that indicate that there is a need of data about the availability and condition of facilities and infrastructure to support the learning of physical education in Elemtary School, Kedu, Temanggung. The study examines the availability and condition of physical education learning facilities in Elemtary School, Kedu, Temanggung. The research method is used using surveys with a quantitative descriptive approach. This research is using survey method by 10 elementary School in Kedu subdistrict Temanggung district. The data collecting technique uses quota sampling. The instruments observations, interviews, observation sheets and documentation. Data collection includes the number of tools, number of tooling, number of facilities, equipment condition, tool condition, and the condition of facilities in Elemtary School, Kedu, Temanggung. the results of research on the existence and condition of physical education learning tools in Kedu Elementary School Temanggung District 10 schools in the category of Enough (100%), and for its condition 85.7% in Good condition. The existence and condition tools 9 Schools in the category of Enough (90%), there is 1 school in the category of Less (10%) and for the condition is 75.8% in Good condition. And for the existence and condition facilities 5 schools in the category of Good (50%), 4 schools in the category of Enough (40%) and 1 School in Category Less (10%) for kndisinya 85.7% of facilities are in good condition.. In this research, the facilities and infrastructures that exist in the elementary school in Kedu sub-district Temanggung are in medium category. The advice that is given by researchers is the government of Temanggung Regency pay more attention to the facilities and infrastructure in the basic district of Kedu and also physical education teachers can maintain and modify the facilities and infrastructures that are in the school.